2001
DOI: 10.1159/000047157
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Fetal Growth Restriction According to Constitutional Growth Potential

Abstract: Identification of newborn babies with fetal growth restriction remains a problem both from the multi-factorial aspect of fetal growth and from statistical definition. Besides the usual terms: ‘Small for gestational age’ (SGA) and intrauterine growth retardation (IUGR), often used synonymously, the term ‘fetal growth retardation’ was recently introduced in reference to the genetic growth potential of infants. From a sample of 72,000 births, we have designed a statistical model in order to estimate the expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 19 publications
2
89
0
3
Order By: Relevance
“…Edwards et al [1] demonstrated in a study comparing two groups of teenagers whose high BMI divided according to weight gain pergestationnel that macrosomia was significantly more frequent when weight gain exceeded 8 kg during pregnancy; our results confirm this study and is widely approved by Boyd et al [16] how showed that the risk of macrosomia increases markedly with excessive weight gain in addition an earlier study on a Chinese population. [17] that has largely proved the risk of the occurrence of macrosomia was two fold for women who gain more weight during pregnancy then Kabali et al [15] affirmed that fetal macrosomia was significantly higher among women who gained excessive gestational weight.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…Edwards et al [1] demonstrated in a study comparing two groups of teenagers whose high BMI divided according to weight gain pergestationnel that macrosomia was significantly more frequent when weight gain exceeded 8 kg during pregnancy; our results confirm this study and is widely approved by Boyd et al [16] how showed that the risk of macrosomia increases markedly with excessive weight gain in addition an earlier study on a Chinese population. [17] that has largely proved the risk of the occurrence of macrosomia was two fold for women who gain more weight during pregnancy then Kabali et al [15] affirmed that fetal macrosomia was significantly higher among women who gained excessive gestational weight.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 89%
“…[1] Conversely, women who in late pregnancy less than 50 kg and / or a body mass index less than 20 kg/m2 have weight newborns with weight, height and head circumference have relatively increased risk of having a newborn with a delay of intrauterine growth. The weight to gain during pregnancy in industrialized countries is an important factor associated with fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal growth restriction after accounting for growth potential. A customised definition of restricted growth for the newborns of this study was developed taking into account their constitutional characteristics (30,31) . Maternal and newborn characteristics considered a priori were: gestational age in weeks, maternal and paternal height (in cm) and age (in years), maternal pre-pregnancy weight (in kg), primiparous mother and infant sex.…”
Section: Fetal Growth Assessmentmentioning
confidence: 99%
“…Não obstante, os termos RCIU e PIG são, com freqüência, utilizados como sinônimos e os mesmos limites estatísticos são utilizados para sua identificação. No entanto, cabe destacar a possibilidade de alguns neonatos PIG serem apenas constitucionalmente pequenos, quando analisados segundo seu potencial genético de crescimento, representando a porção final da curva de distribuição normal 2 . O conceito de neonato PIG é, portanto, de definição estatística e a interpretação de seu desenvolvimento deve considerar esse importante fator.…”
unclassified